OXGR1 is a candidate disease gene for human calcium oxalate nephrolithiasis - Majmundar, Amar J.; Widmeier, Eugen; Heneghan, John F.; Daga, Ankana; Wu, Chen Han Wilfred; Buerger, Florian; Hugo, Hannah; Ullah, Ihsan; Amar, Ali; Ottlewski, Isabel; Braun, Daniela A.; Jobst-Schwan, Tilman; et al. (Genetics in Medicine, 2023)
Purpose: Nephrolithiasis (NL) affects 1 in 11 individuals worldwide, leading to significant patient morbidity. NL is associated with nephrocalcinosis (NC), a risk factor for chronic kidney disease. Causative genetic variants are detected in 11% to 28% of NL and/or NC, suggesting that additional NL/NC-associated genetic loci await discovery. Therefore, we employed genomic approaches to discover novel genetic forms of NL/NC. Methods: Exome sequencing and directed sequencing of the OXGR1 locus were performed in a worldwide NL/NC cohort. Putatively deleterious, rare OXGR1 variants were functionally characterized. Results: Exome sequencing revealed a heterozygous OXGR1 missense variant (c.371T>G, p.L124R) cosegregating with calcium oxalate NL and/or NC disease in an autosomal dominant inheritance pattern within a multigenerational family with 5 affected individuals. OXGR1 encodes 2-oxoglutarate (α-ketoglutarate [AKG]) receptor 1 in the distal nephron. In response to its ligand AKG, OXGR1 stimulates the chloride-bicarbonate exchanger, pendrin, which also regulates transepithelial calcium transport in cortical connecting tubules. Strong amino acid conservation in orthologs and paralogs, severe in silico prediction scores, and extreme rarity in exome population databases suggested that the variant was deleterious. Interrogation of the OXGR1 locus in 1107 additional NL/NC families identified 5 additional deleterious dominant variants in 5 families with calcium oxalate NL/NC. Rare, potentially deleterious OXGR1 variants were enriched in patients with NL/NC compared with Exome Aggregation Consortium controls (χ2 = 7.117, P = .0076). Wild-type OXGR1-expressing Xenopus oocytes exhibited AKG-responsive Ca2+ uptake. Of 5 NL/NC-associated missense variants, 5 revealed impaired AKG-dependent Ca2+ uptake, demonstrating loss of function. Conclusion: Rare, dominant loss-of-function OXGR1 variants are associated with recurrent calcium oxalate NL/NC disease.
CRIS-Team Scopus Importer:2023-02-03
Keywords: Alpha-ketoglutarate; Calcium oxalate; Genetics; Nephrolithiasis